Strategic planning of urban neighborhoods (case study: Abshar neighborhood of Tehran City) - Zeinab Adeli; Hamed Mohammadibeyragh; Minoo Baghbani (مهندسی و مدیریت ساخت, 2022)
After the emergence of problems and inconsistency, as well as the failure to achieve the intended goals in the intervention policies in the cities, following the comprehensive planning of the cities, people's participation and a multi-sectoral approach were taken into account in strategic planning based on local comparisons. The realization of the bottom-up perspective in planning makes it necessary to start planning from the neighborhood scale. In this article, in order to solve the problems and complexities of Abshar neighborhood, the strategic planning of this neighborhood has been developed. This research is among applied research based on descriptive-analytical method. In order to collect information from library and other documents, direct observation and collection, holding meetings in the form of focused group discussions, interviews with residents and officials of the municipality of District 12 have been used. The assessment of the neighborhood situation has been done using the SWAT technique. The work process is such that, after the general examination and knowledge of the neighborhood in the physical, social, economic and institutional fields based on the defined indicators, with the use of individual interviews and focused group discussions, the weaknesses, strengths, and opportunities and neighborhood threats were identified. Also, the list of assets and funds of the neighborhood was extracted. By prioritizing the issues and problems of this neighborhood, based on this table and the results obtained from focused discussions and interviews, the perspective of the neighborhood was defined. In order to realize this vision, goals, policies, strategies and finally an action plan were defined.